Pragmatics of speech actions - Sbisà, Marina (Handbooks of pragmatics, 2013)
This volume provides extensive critical information about current discussions in the study of speech actions. Its central reference point is classic speech act theory, but attention is also paid to nonstandard developments and other approaches that study speech as action. The first part of the volume deals with main concepts, methodological issues and phenomena common to different kinds of speech action. The second part deals with specific kinds of speech actions, including types of illocutionary acts and some discourse and conversational phenomena.